Rediscovering fosfomycin in its 50th anniversary (1969-2019) - Pedro Romero Pérez (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
2019 marks the 50th anniversary of the discovery of fosfomycin, an antibiotic widely used in urological and systemic diseases. As a urologist, I have some reasons to dedicate this short article to it: